Criminal Law and Neuroscience: Theory and Practice in the Italian Perspective - Grandi, Ciro (International Journal of Criminology and Sociology, 2022)
The debate on the impact on criminal justice of the empirical evidence offered by techniques of brain exploration and behavioral genetics shows no sign of diminishing, fed by literature now boundless and by case law in constant growth. In the Italian system, the impact of neuroscience at trial is still rather limited and substantially confined to its sedes naturalis, that is to say, the insanity defense. Even in this area, however, there is a very cautious, if not sometimes distrustful, attitude on the part of the courts, still doubtful about the epistemological reliability of neuroscientific evidence. The interdisciplinary dialogue is called upon to help overcome uncertainties and resistance, to avoid the underestimation of data endowed – albeit in a complementary and integrative function – with an increasingly objective value. Summary: 1. Foreword. - 2. Neuroscience: an outline. - Neuroscience and criminal law in the light of the radical-revolutionary model. - 4. Neuroscience and criminal law in the light of the moderate-compatibilist model. - 5. An overview of the use of “neuroscientific evidence” in practice - 6. Neuroscience and the evaluation of criminal capacity: a first assessment. - 7. The (still) limited impact of neuroscience in the Italian criminal trial. Diagnosis and prognosis. – 8. Conclusions.